EFEKTIVITAS SALEP EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) TERHADAP PROSES PENYEMBUHAN LUKA GORES PADA KELINCI - Ferry Effendi; Padmono Citroreksoko; Deo Subagyo (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2016)
Anredera cordifolia (Ten.) Steenis that is known by the name of binahong leaves have medicinal properties traditionally as wound healing. This study aims to determine the effectiveness of leaf binahong extract ointment on graze and to know the effectiveness of the leaf binahong extract ointment as wound healing. This research used experimental research method. Simplicia powder of binahong leaf was extracted using a maceration method. The result of maceration extracted by using a rotary evaporator, the extract obtained are formulated into ointments. Binahong leaf extract ointment made within 5 concentrations that is a concentration of 20%, 25%, 30%, 35% and 40%. The subject of research in the form of a rabbits that amount 3 tails were divided into 7 treatment groups ie negative control (ointment base), positive control (Betadine ointment), ointments leaf extract binahong 20%, ointment leaf extract binahong 25%, ointment leaf extract binahong 30%, ointment binahong 35% leaf extract and leaf extract ointment binahong 40%. Rabbits are scarred on the back with a wound length of 2 cm. Ointment leaf extract with various concentrations carried out the effectiveness test against the healing of scratch on the back of a rabbit that has been injured. On testing ointment was done organoleptic test, homogeneity test and pH test. The data were processed statistically using ANOVA analysis with SPSS method. Results of the research and the results of statistical analysis that extract ointment. Binahong leaf had effectivity on a scratch wound. Binahong leaf extract ointment concentration of 20%, 25% and 30% have given the effect of wound healing, where as the concentration of 35% and 40% give a more effective healing effect. Effects similar to the positive control, namely ointment binahong leaf extract with a concentration of 35%, whereas the leaf extract ointment binahong 40% have the best effect.